Loss of Color by Afterimage Masking. (May 2013) - Takahashi, Kohske; Yamada, Shun'ya; Ono, Fuminori; Watanabe, Katsumi
When two images, one depicting colored disks and the other depicting colored windmill patterns, are displayed in succession, the color of the windmills is perceptually replaced by black. The illusion is striking. Experiments confirmed (1) that the luminance contrast between the target patterns and the background must be large and (2) that the disks and windmills must be static on the retina and in register. The illusion is weakened when the windmills and disks have different colors.